E-tourism: A communication strategy of Yogyakarta's tourism potential marketing in industrial revolution 4.0 era - Aw, Suranto; Agustinova, Danu Eko; Fitriana, Kurnia Nur; Arif, Nursida; Wulansari, Nur Lailly Tri (Universitas Negeri Yogyakarta, 2023)
Digital technology development during the industrial revolution 4.0 era can be a way to promote tourism. Nowadays, the concept of e-tourism (electronic tourism) has become popular in Indonesia. E-tourism in itself is an IT-based system applied in tourism sector that provides various information digitally. This research aims to describe a communication strategy in marketing Yogyakarta's tourism potential through e-tourism. This research uses descriptive-qualitative approach with library research method. The Special Region of Yogyakarta (DIY) has a vast variety of tourist attraction, ranging from historical places to shopping districts. Those tourism potential have drawn many tourists, locals and foreigners alike. As an effort to raise tourism visit, the DIY Tourism Department has implemented website and mobile based applications. Such method to promote tourism digitally is a right choice since e-tourism provides easiness for tourists in accessing tourism information as well as making activity plan.